2013
DOI: 10.1021/jm400351a
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Selective and Potent Inhibitors of Fibroblast Activation Protein and Prolyl Oligopeptidase

Abstract: Fibroblast activation protein (FAP) is a serine protease selectively expressed on reactive stromal fibroblasts of epithelial carcinomas. It is widely believed to play a role in tumor invasion and metastasis and therefore to represent a potential new drug target for cancer. Investigation into its biological function, however, has been hampered by the current unavailability of selective inhibitors. The challenge has been in identifying inhibitors that are selective for FAP over both the dipeptidyl peptidases (DP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 39 publications
(75 reference statements)
2
78
0
Order By: Relevance
“…However, Z-GP-DAVLBH was resistant to hydrolysis by DPP-IV, the closest homolog of FAPα (Supplemental Figure 2). Interestingly, we found that prolyl endopeptidase (PEP), a cytosolic prolyl oligopeptidase that possesses FAPα-like endopeptidase activity (18), showed approximately 1/7 of the hydrolytic activity jci.org Volume 127 Number 10 October 2017…”
Section: Resultsmentioning
confidence: 99%
“…However, Z-GP-DAVLBH was resistant to hydrolysis by DPP-IV, the closest homolog of FAPα (Supplemental Figure 2). Interestingly, we found that prolyl endopeptidase (PEP), a cytosolic prolyl oligopeptidase that possesses FAPα-like endopeptidase activity (18), showed approximately 1/7 of the hydrolytic activity jci.org Volume 127 Number 10 October 2017…”
Section: Resultsmentioning
confidence: 99%
“…(2) targeting the CAF-carcinoma cell interaction through CXCL12, CXCR4, CCL7, FGF, Gal-1, Smo, HGF, CCL2, IGF-II, CAIX, TN-C, POSTN, and TGF-β [76]; (3) targeting CAF-endothelial cell interactions through VEGF, FGFs, CXCL12, and PDGFs; (4) targeting the CAF-modulated ECM remodeling by inhibiting caveolin-1 and MMPs (and someone has tried to develop new techniques to alleviate solid stress or stiffness to increase tumor perfusion) [77]; (5) targeting CAF-induced inflammation and immune escape through CXCL1, CXCL2, CXCL12, CXCL14, COX-2, CCL2, CCL5, IL-1β, and TGF-β; (6) targeting CAFmediated anti-immune responses, the design of FAP-based therapeutic approaches to target CAFs has been developed, such as FAP neutralizing antibodies, inhibitors [78], prodrugs [79], and DNA vaccines [80]; and (7) targeting DNA methylation in CAFs may be another approach to preferentially block CAFs' function [34]. At present, two kinds of approaches targeting DNA methylation are available: methyl donor modifiers (folate, betaine, and choline) and methyltransferase inhibitors (nucleoside inhibitors: 5-azacytidine, 5-aza-2-deoxycytidine, and zebularine; and non-nucleoside inhibitors: procaine, procainamide, EGCG, and RG108) [81].…”
Section: Discussionmentioning
confidence: 99%
“…These adipocytes were incubated with full-length or FAP-cleaved FGF-21 at 500 ng/mL. FGF-21 was pre-incubated with PBS or recombinant FAP (substrate: enzyme ratio = 5:1) for 2 h, with or without FAP-selective inhibitor ARI-3099 [32] at 5 µM. Immunoblots of FGF-21, Erk, phosphorylated Erk (p-Erk) ACC, p-ACC, PGC-1α and β-actin were performed on lysates of tissues or of cells.…”
Section: Immunoblottingmentioning
confidence: 99%